(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides information on the study and scientific justification of the effectiveness of the elasticity of students of the Faculty of Physical Culture by the author’s style through the type of sports gymnastics in which Complex-Coordinated sports are distinguished. The study divided the exercise kotegoria into six groups to develop flexibility and compiled a set of exercises on groups and their sequence.